2010
DOI: 10.1590/s1809-98232010000300005
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco para mortalidade de idosos com infecção do sítio cirúrgico

Abstract: Purpose: to relate risk factors for mortality in elderly patients undergoing abdominal surgery with surgical site infection. Method: it is a descriptive quantitative crosssectional retrospective study, performed in teaching hospital in Curitiba-PR. The sample period was from January 1999 to December 2008. Data were collected through structured instrument in secondary sources: Registration Service Infection Control and the patient's chart. A sample consisted of records of 114 elderly patients with REV. BRAS. GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…During the study, patients were at higher risk for mortality if they were hospitalized in the internal medicine unit, were elderly (>60 years old), were on hemodialysis, or required mechanical ventilation or orotracheal intubation. It has been previously reported that older patients are more likely to develop hospital infections because of the physiological changes associated with aging, a decline in immune response, and the need for invasive procedures 6 . When patients are subjected to procedures such as mechanical ventilation, orotracheal intubation, and hemodialysis, their microbiota becomes unbalanced and protective barriers are broken, thereby increasing the chance of colonization and nosocomial infection 7 .…”
mentioning
confidence: 99%
“…During the study, patients were at higher risk for mortality if they were hospitalized in the internal medicine unit, were elderly (>60 years old), were on hemodialysis, or required mechanical ventilation or orotracheal intubation. It has been previously reported that older patients are more likely to develop hospital infections because of the physiological changes associated with aging, a decline in immune response, and the need for invasive procedures 6 . When patients are subjected to procedures such as mechanical ventilation, orotracheal intubation, and hemodialysis, their microbiota becomes unbalanced and protective barriers are broken, thereby increasing the chance of colonization and nosocomial infection 7 .…”
mentioning
confidence: 99%